2016
DOI: 10.18632/oncotarget.8610
|View full text |Cite
|
Sign up to set email alerts
|

CD74 and intratumoral immune response in breast cancer

Abstract: CD74 (invariant chain) plays a role in MHC class II antigen presentation. We assessed CD74 and MHCII expression in tumor cells, as well as CD8, CD4, and CD68 tumor infiltrating leucocyte (TIL) density by immunohistochemistry in a cohort of 492 breast cancer patients. CD74 expression was associated with poor prognostic markers including patient age, tumor grade, ER status, non-Luminal A subtypes, and with MHCII expression and higher TIL densities, particularly in the Basal-like subgroup. Univariate analysis sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(38 citation statements)
references
References 47 publications
5
33
0
Order By: Relevance
“…The relation between PD-L1 and the levels and localization of CD8, CD4, and CD68 TIL was assessed (Figure 3 ). As reported in our prior studies [ 24 , 25 ], the intraepithelial densities of all three TIL subsets were higher in triple negative subsets (TNNB and Basal-like) compared to the rest of the cohort. PD-L1 positive status tended to be associated with higher TIL density in all subsets.…”
Section: Resultssupporting
confidence: 84%
“…The relation between PD-L1 and the levels and localization of CD8, CD4, and CD68 TIL was assessed (Figure 3 ). As reported in our prior studies [ 24 , 25 ], the intraepithelial densities of all three TIL subsets were higher in triple negative subsets (TNNB and Basal-like) compared to the rest of the cohort. PD-L1 positive status tended to be associated with higher TIL density in all subsets.…”
Section: Resultssupporting
confidence: 84%
“…It indicated that CD44 expression may regulate anti-tumor immunity by suppressing CD4 expression. CD74, a transmembrane glycoprotein, associates with the major histocompatibility complex (MHC) Class II and plays important roles in the intratumoral immune response [2729]. CD74 was overexpressed in thyroid malignancy, malignant pleural mesothelioma, and head and neck squamous cell carcinomas, and it is associated with advanced tumor stage [3032].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, among the transcripts most differentially expressed between K14.GFP+ and K14.GFP− cells, we found both new and known metastasis-associated genes ( Table 2 ). Genes including metallothionein-2 ( Mt2 ) [ 29 , 30 ], transmembrane glycoprotein nonmetastatic B ( Gpnmb ) [ 31 ], caveolin 1 ( Cav1 ) [ 32 ], Col6A1 [ 26 , 27 ], HLA-DR antigens-associated invariant chain ( Cd74 ) [ 33 , 34 ], secretory leukocyte peptidase inhibitor ( SLPI ) [ 35 ], carbonic anhydrase ( Car9 ), amphiregulin ( Areg ) [ 36 38 ], and peripheral myelin protein 22 ( PMP22 ) [ 39 ] have previously been reported in association with invasive and/or metastatic phenotypes or as markers for poor prognosis in human breast cancer.…”
Section: Resultsmentioning
confidence: 99%